Søndag efter søndag: Johannes Sløks forkyndelse igennem 40 år - Brorson, Mikael (Dansk Teologisk Tidsskrift, 2024)
This article explores the Aarhus theologian Johannes Sløk’s sermon guides, published in Præsteforeningens Blad in 1980 and 1982 respectively, in order to cast light on the question of continuity in Sløk’s thought and the ‘narrative turn’ in his authorship. The article consists of two parts: i) a diachronic reading and comparison of Sløk’s sermon guides vis-a-vis Sløk’s sermons from the 1940’s, to show how Sløk’s theology develops in this time span, and ii) a synchronic reading of the sermon guides, which points to three decisive theological topics in the sermon guides that are also constitutive for Sløk’s thought in general. Thus, the article consolidates the position in Sløk research that although a development and a ‘narrative turn’ does indeed take place in Sløk’s theology, this is not to be considered a break, but rather, a refinement.